PROBLEMATIKA MENCIPTAKAN WIRAUSAHA MUDA - Nuzulul Qurnain (IQTISHADIA Jurnal Ekonomi & Perbankan Syariah, 2015)
Unemployment and poverty in Indonesia became one of the problems is endless. Number of Students dropouts and educated unemployment also exacerbate the economic downturn in Indonesia. annually, University chip in alumni who are not absorbed by the employment. Not again secondary students who drop out or do not continue school. One of efforts that can be done to cultivate enthusiasm and motivation to entrepreneurship. entrepreneurship education is not only necessary but must be given to the public, good for basic education,secondary  to College in order to shape the mindset of the younger generation to entrepreneurship. Support from all parties, such as family, community, education World, government, business world and industry can also increase the number of young entrepreneurs in Indonesia. Various efforts, special are needed to resolve the problems in creating entrepreneurs.